PENGARUH TEKSTUR DAN KELEMBABAN TANAH TERHADAP POPULASI LARVA LEPIDIOTA STIGMA PADA PERTANAMAN TEBU DI KABUPATEN SLEMAN - , RADIYANI MIRZA ALFARISI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was aimed to know the determine the distribution of larval populations of L. stigma on sugar cane plantations in Sleman. Observations carried out by determining the location of population sampling in sugarcane plantations in Sleman district in ten places (Sambiroto, Grenjeng A, Grenjeng B, Tempelsari A, Tempelsari B, Njaplaksari, Pronanggan, Pundungrejo, Selokan, and Seturan ) of the month of February to June. Observation parameters used are larvae (L. stigma), the number of individuals (head/m2), depth (cm), and soil moisture (%). The results showed that the patterns of larval dispersal L. stigma on sugar cane plantations in Sleman were clustered. The highest number of individuals was found in Njaplaksari, while those with the lowest number of larvae was on Tempelsari B. Soil with a high content of dust fraction (29.81%) resulted in high number of larval populations of L. stigma. Vertical mobility of larval L. stigma was influenced by soil texture class and soil moisture. Larvae was tend to be found in shallow depth when the fraction of the dust or soil moisture was higher. Otherwise, larvae was tend to be found deeper when the fraction of the sand was higher.